The effect of politician denialist approach on COVID-19 cases and deaths - Rodrigo Gomes de Arruda; Tatiane Menezes; Joebson Maurilio Alves dos Santos; Antonio Páez; Fernando Lopes (EconomiA, 2021)
Concern over the high rate of contagion of COVID-19 has prompted world authorities to use the strategy of isolation and social confinement as the main non-pharmacological weapon against the disease that has rapidly killed millions of people worldwide. However, there is evidence that the denialist rhetoric of the Brazilian President has negatively influenced people's behavior in relation to obedience to confinement and social isolation measures. The aim of this study is to analyze the correlation between the Brazilian President's denialist rhetoric and the low adherence to social distancing measures and the subsequent increase of new coronavirus cases and deaths. Daily data on the level of contamination by COVID-19, social distancing and information from Brazilian states between the months of February and May 2020 were used. Taking into consideration the differences between the federal government of Brazil and state governors about the severity of the pandemic and the importance of social distancing, the article uses the Instrumented Difference-in-Differences approach, suggested by Duflo (2001), to obtain the causal impact of reduced social distancing, resulting from Presidential denialist rhetoric, in mitigating COVID-19 cases and deaths, taking into account the relationship between the president of the republic and the states as an instrument. The results suggest that the Brazilian average Social Isolation Index increased from 39.77% to 51% between February 1st and May 18th, 2020, the country would have had approximately 318,850.03 fewer cases of COVID-19, and more than 10.000 lives would have been saved.
Keywords: 330; COVID-19; Denialist approach; Instrumented difference-in-difference